2011
DOI: 10.1248/jhs.57.432
|View full text |Cite
|
Sign up to set email alerts
|

Citidine-5-diphosphocholine Ameliorates the Impairment of Spatial Memory Induced by Scopolamine

Abstract: The memory enhancing effects of orally administered citidine-5-diphosphocholine or citicoline (CDPcholine) on memory impairment without neuronal cell death are still unknown. We investigated the effects of CDP-choline on memory disturbance induced by scopolamine using an eight-armed radial maze task. Orally repeated administration of CDP-choline or histidine significantly restored the errors impaired by scopolamine. CDP-choline may increase hippocampal and neocortical acetylcholine levels. These results sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Citicoline attenuates vascular cognitive impairment in animal models of brain ischemia [131]. Citicoline also prevents amnesia induced by scopolamine [132][133][134]. Citicoline acts as a drug able to enhance memory in animals with memory deficits from different causes [135][136][137][138][139][140].…”
Section: Experimental Datamentioning
confidence: 99%
“…Citicoline attenuates vascular cognitive impairment in animal models of brain ischemia [131]. Citicoline also prevents amnesia induced by scopolamine [132][133][134]. Citicoline acts as a drug able to enhance memory in animals with memory deficits from different causes [135][136][137][138][139][140].…”
Section: Experimental Datamentioning
confidence: 99%
“…Authors suggested that this effect is mediated by drug actions on neurotransmission. Takasaki et al [ 370 ] suggest that citicoline has ameliorative effect on the impairment of spatial memory induced by scopolamine, reducing the neuronal death and improving the impaired cholinergic signal. Citicoline acts as a memory-enhancing drug, and this effect is particularly marked in animals with memory deficits [ 371 ].…”
Section: Pharmacological Actionsmentioning
confidence: 99%
“…Posteriormente, Mosharrof y Petkov [ 369 ] demostraron que la citicolina en dosis de 100 mg/kg prevenía completamente la amnesia inducida por la escopolamina, así como la asociación de 50 mg/kg de citicolina con 500 mg/kg de piracetam, produciendo, además, un incremento significativo de la retención, y los autores sugieren que este efecto viene mediado por las acciones del fármaco sobre la neurotransmisión. Takasaki et al [ 370 ] sugieren que la citicolina tiene un efecto mejorando el deterioro de la memoria especial inducido por la escopolamina, reduciendo la muerte neuronal y mejorando la señal colinérgica deteriorada. La citicolina actúa como un fármaco potenciador de la memoria y este efecto es particularmente pronunciado en animales con déficits de memoria [ 371 ].…”
Section: Acciones Farmacológicasunclassified